(untitled) (Annals of Medical Research, 2021)
Aim: A proper percutaneous renal access is the most crucial step in the procedure. This retrospective study aims to compare the efficacy and safety of monoplanar and biplanar access in PCNL operations.Material and Methods: The study included a total of 72 patients with single kidney stones larger than 20 mm in diameter, who underwent PCNL surgery between September 2016 and May 2018. The patients were divided into two groups monoplanar access (Group 1) and biplanar access group (Group 2). There were 38 and 34 patients in Groups 1 and 2, respectively. Stone and urinary system characteristics, operation parameters and postoperative findings of all patients were recorded.Results: There was no statistically significant difference between two groups in terms of mean age, sex and kidney stone size. Mean operation duration was 64.3 ± 21.7 minutes in group 1 and 61.8 ± 27.4 minutes in group 2 (p=0.494). A statistically significant difference was observed between the groups in terms of mean fluoroscopy time, which was 3.46±1.24 minutes in group 1 and 4.45±1.57 in group 2 (p=0.008). The mean puncture time was signiﬁcantly lower in group 1 (p=0.042). The stone-free rate was 78.9% and 82.3% in groups 1 and 2, respectively (p=0.87). There was no statistically significant difference between the groups in terms of complications (p=0.72). Conclusion: Both access techniques have been found to similar success and complication rates in PCNL operations. However, the fluoroscopy duration and puncture time are shorter in cases where monoplanar access is established; which may be effective in preferring this technique.